Casuistry an Social Category Bias. (article). - Norton, Michael I.
This research explored cases where people are drawn to make judgments between individuals based on questionable criteria. In particular those individuals' social group memberships. We suggests that individuals engage in casuistry to mask bias decision making, by recruiting more acceptable criteria to justify such decisions. We present 6 studies that demonstrate how casuistry licenses people to judge on the basis of social category information but appear unbiased -to both others and themeselves.-while doing so . In 2 domains (employment and college admissions decisions), with 2 social categories (gender and race), and with 2 motivations (favoring an in-group or out-group) , the present studies explored how participants justify decisions biased by social category information by arbitrarily inflating the relative value of their preferred candidates' qualifications over those of competitors. -- ( from the author)